effective use of feedback the concurrent foreign (immediate) and the final at the speed of learning transmitter tennis skill in front of the Supreme fourth - Ghina, Saeed (Journal of Physical Education, 2013)
The success of teaching-learning process in the field of teaching physical education and sport does not depend on the student and their capabilities, but also goes beyond that to include the teacher and his handling of the row, and abilities to accomplish the interaction between him and the learner and this does not only come to the optimum use of feedback according to logical rules correct. The importance of research came to identify the impact of the use of feedback the concurrent foreign (immediate) and the final on the one hand, and see which is more effective in the speed of learning the technical performance of a transmitter tennis skill in front of the highest in the game of volleyball. The researcher has been assumed that there are significant differences in favor of tests posteriori for the two experimental groups, and in favor of the experimental group practiced feedback concurrent, was selected fourth-graders Al-Thoura preparatory for boys in Maysan province for the academic year 2012/2013 and of the 110 students as a community to search were identified 28 student as a sample of research and divided into two experimental rate (14) students per group, researcher has concluded the effectiveness of simultaneous use of feedback, has recommended the adoption and application of the rest of the skills of the game of volleyball and other games .